CARTILHA EDUCATIVA EM SAÚDE REPRODUTIVA: ÊNFASE NAS GESTANTES QUE BUSCAM A CONTRACEPÇÃO DEFINITIVA - Kaufmann, Andrio de Souza Gonçalves (2020)
Introduction: Reproductive planning actions are aimed at strengthening sexual and reproductive rights. They are based on clinical, preventive, educational actions, offering information and methods to regulate fertility. The Law nº 9263 regulates family planning and allows voluntary sterilization in men and women with full civil capacity, over 25 years of age or, at least, with two living children, and even when pregnancy poses a risk to life or health of the woman or the future fetus, and who wish this intervention for reproductive health. There are other impacting aspects in the decision making of the best contraceptive method to be used by women, such as socioeconomic, cultural, age, psychological, spiritual and clinical factors, which motivate, however, the decision for permanent contraception and which should be considered in this decision. Objectives: To develop an educational booklet on reproductive health for pregnant women seeking a public hospital service and to investigate the clinical and epidemiological profile of pregnant women who wish to perform definitive contraception in a public hospital service. Method: For the elaboration of the educational booklet, the following steps were considered: situational diagnosis, literature review for the selection, creation and chronological organization of the content. Regarding scientific research, it is configured as a descriptive and exploratory quantitative approach, with a retrospective documentary character, carried out through the attendance sheets of the clinical and epidemiological profile of pregnant women who seek the Family Planning Commission of a public hospital service and wish to carry out the definitive contraception. The data collection period was from October 2019 to April 2020 and the data were structured in spreadsheets using Excel software version 2007, and analyzed using descriptive statistics. Results: To meet the first objective, the process of building the educational booklet on reproductive health was reported, with an emphasis on pregnant women seeking permanent contraception. The process of preparing the technological product took place in stages, from identifying the reasons that lead pregnant women to choose the performance of definitive contraception; know the clinical and epidemiological profile, through field research; approval by the Hospital Ethics Committee and Health Research Ethics Committee; select scientific material, elaborate layout and text to appear in the educational booklet. Regarding the second objective, the data showed that, predominantly, the pregnant women were over 31 years of age, were white in color, with schooling over eight years of study, 15 married or single, but with a stable union, living with a partner and child(s) and with family income above three minimum wages. Most of these women used contraceptive methods before pregnancy, an oral hormonal type. All pregnant women had a history of previous pregnancy, and most had two or more live children. It is noteworthy that most births were due to cesarean delivery. Product generated and applicability: The product generated through this study was an educational booklet entitled “Educational Booklet in Reproductive Health”. This product is characterized as a health management tool, especially in the Maternal and Child construct, due to the understanding that the development of an educational care technology is considered a transforming tool in the management processes of health services, guide knowledge about care practices. Thus, its applicability in the context of pregnant women dimension national reproductive health policies, enabling access to guidance on this approach.